Experimental studies of boronophenylalanine (10BPA) biodistribution for the individually tailored application of boron neutron capture therapy (BNCT) for malignant melanoma treatment - Carpano, Marina; Perona, Marina; Rodríguez, Carla Beatriz; Nievas, Susana Isabel; Olivera, María; Santa Cruz, Gustavo Alberto; Brandizzi, Daniel; Cabrini, Romulo Luis; Pisarev, Mario Alberto; Juvenal, Guillermo Juan; Dagrosa, María Alejandra (Elsevier Science Inc, 2015)
Fil: Carpano, Marina. Comisión Nacional de Energía Atómica. Gerencia de Area de Aplicaciones de la Tecnología Nuclear. Gerencia de Radiobiología (Centro Atómico Constituyentes); Argentina